The Effect of Kaizen, Lean Accounting, and Six Sigma on Internal Audit Effectiveness with SBSC as Moderator - Helmy Aulia Rachman; Meilenia Rahma Salisa; Fajar Dwi Kuncoro (Economic and Business Horizon, 2026)
This study investigates the effectiveness of internal audit functions in state-owned enterprises particularly in addressing ongoing fraud issues and deficiencies in internal control systems. The primary objective is to empirically evaluate the impact of kaizen, lean accounting, and six sigma on internal audit effectiveness, while incorporating the Sustainability Balanced Scorecard (SBSC) as a moderating variable. The research adopts a quantitative explanatory approach, utilizing purposive sampling to obtain data from 100 employees within State-Owned Enterprises. The analysis is conducted using Moderated Regression Analysis (MRA) with SPSS software. The results indicate that kaizen, lean accounting, and six sigma each exert a positive and statistically significant influence on internal audit effectiveness. Among these approaches, six sigma emerges as the most influential factor, as reflected by its highest coefficient and level of significance. In addition, SBSC is found to significantly enhance the relationships between the independent variables and internal audit effectiveness, underscoring its role in strengthening sustainability-based performance evaluation. The findings highlight that the integration of continuous improvement practices with sustainability-oriented frameworks can enhance the quality and effectiveness of internal audits.